An integrated host-microbiome response to atrazine exposure mediates toxicity in Drosophila - James B. Brown (Nature Portfolio, 2021)
Brown et al. apply integrated omics and phenotypic screening to assess the role of the gut microbiome in modulating host resilience in Drosophila melanogaster. They find that Acetobacter tropicalis in gnotobiotic animals, is sufficient to rescue increased atrazine toxicity, which could pave the way for biotic strategies to improve host resilience to environmental chemical exposure.